Analysis of Convenience, Service Features and Risk in the Decision to Use the Generation Z ShopeePay Payment System in the Wates District Area - Nuzila, Melinda Ifa; Rantanto, Sigit (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : Aims to explore and analyse the convenience, service features, and risks of Generation Z in Wates District towards using ShopeePay as a payment method. Ease and service features can access risks of using ShopeePay is a digital payment tool that can facilitate transactions. Design/Methode/Approach : The research can use a quantitative causality approach. Processing with nonprobability sampling method with accidental technique, and distributing questionnaires to 40 respondents, using goggle form in the Wates District area. Research Finding : This finding shows that Generation Z in Wates District tends to prefer the ShopeePay application as a payment that can be used easily. The availability of simple navigation features makes the payment process fast. Risks in the use of ShopeePay among Generation Z such as not realizing the importance of maintaining personal information. Theoretical contribution/Originality : The theoretical contribution of this analysis can provide new insights in understanding the factors that influence Generation Z's use of ShopeePay. Practitionel/Policy implication : Meanwhile, the practical implications can help financial managers and other stakeholders in formulating more effective strategies to meet the needs of Generation Z in district Wates. Research limitation : However, this study has some limitations that need to be considered. The sample used was limited to Generation Z in Wates Sub-district, so the results may not be generalizable to a wider population. This study relied on data collected through questionnaires, which could be affected by respondent bias and limitations in their understanding of the questions asked